FUNDAMENTAL FACTORS OF FIRM VALUE: EVIDENCE FROM THE CEMENT INDUSTRY IN INDONESIA - Kusumowardhani, Widyarti (Jurnal Inovasi Ekonomi)
This study aims to analyze the factors which influence firm value. This study uses multiple regression analysis and takes data from three cement companies listed on the IDX. The results of this study concluded that companies must be efficient and keep the debt ratio to maintain the firm value.